The Role of Mathematics Education in Improving Problem Solving Abilities in the Era of Industrial Revolution 4.0: Indonesia - Djafar, Sri Maryani J.; Mukadam, Aisah; Limpudong, Rena; Laurestabo, Risti; Makwan, Gautam (CV. Edutechnium Indonesia, 2024)
The industrial revolution 4.0 brings many aspects of change that need to be addressed as a challenge that must be faced, especially in mathematics education. According to the OECD, in the field of mathematics, around 71% of students do not reach the minimum competency level in mathematics. This means that there are still many Indonesian students who have difficulty dealing with situations that require problem-solving skills using mathematics. This study uses a library approach with data sources derived from several articles and to support this research also conducted searches via the internet and books. After the data is collected, data processing is carried out, then data analysis is carried out using descriptive analysis. Data collection techniques used are primary data and secondary data. The data source comes from several articles, namely the work of Maifit Hendriani, Silfi Melindawati and Afri Mardicko with the title